Iceball growth 3D simulation model based on finite element method for hepatic cryoablation planning - Shengwei Li; Yumeng Zhang; Fanyu Zhou; Sheng Xu; Yufeng Wang; Lin Cheng; Zhixin Bie; Bin Li; Xiao-Guang Li (BMC Gastroenterology)
Abstract Background Cryoablation simulation based on Finite Element Method (FEM) can facilitate preoperative planning for liver tumors. However, it has limited application in clinical practice due to its time-consuming process and improvable accuracy. We aimed to propose a FEM-based simulation model for rapid and accurate prediction of the iceball size during the hepatic cryofreezing cycle. Methods A 3D simulation model was presented to predict the iceball size (frozen isotherm boundaries) in biological liver tissues undergoing cryofreezing based on the Pennes bioheat equation. The simulated results for three cryoprobe types were evaluated in the ex vivo porcine livers and clinical data. In ex vivo experiments, CT-based measurements of iceball size were fitted as growth curves and compared to the simulated results. Eight patient cases of CT-guided percutaneous hepatic cryoablation procedures were retrospectively collected for clinical validation. The Dice Score Coefficient (DSC) and Hausdorff distance (HD) were used to measure the similarity between simulation and ground truth segmentation. Results The measurements in the ex vivo experiments showed a close similarity between the simulated and experimental iceball growth curves for three cryoprobe models, with all mean absolute error<2.9 mm and coefficient of determination>0.85. In the clinical validation, the simulation model achieved high accuracy with a DSC of 0.87 ± 0.03 and an HD of 2.0 ± 0.4 mm. The average computational time was 23.2 s for all simulations. Conclusion Our simulation model achieves accurate iceball size predictions within a short time during hepatic cryoablation and potentially allows for the implementation of the preoperative cryoablation planning system.